Solution of Riemann problem of conservation laws in van der Waals gas - Gupta P.; Chaturvedi R.K.; Singh L.P. (My University, 2025)
The present study is concerned with the analytical solution of Riemann problem for conservation laws of van der Waals gas. By utilizing Rankine–Hugoniot conditions and Lax entropy condition, we derive classical wave solution of Riemann problem and analyze their properties. Also, it is observed here that van der Waals gasdynamics system is more complex in comparison to ideal gasdynamics case. Further, the effect of presence of intermolecular forces of attraction between the particles and variation of covolume of the gas on the density and velocity distribution across the simple wave, shock wave and contact discontinuities is discussed. © 2022 Informa UK Limited, trading as Taylor & Francis Group.